Trust and Perceived Risk toward Actual Online Purchasing: Online Purchasing Intention as Mediating Variable - Septi Diana Sari; Ratri Nurina Widyanti; Inon Listyorini (Integrated Journal of Business and Economics (IJBE), 2020)
This research aims to test the influence of trust and perceived risk on Actual Online Purchasing (AOP) either directly or through Online Purchase Intention (OPI) as a mediating variable. Purposive Random Sampling used in this research with 100 respondents who have searched product through the E-Commerce website (B2C & C2C). This research uses Structural Equation Modelling (SEM) model with SmartPLS 3 program. The results of the test showed that Security practice and Privacy Concern have a negative effect on Perceived Risk, which subsequently Perceived Risk has a negative effect on OPI. However, OPI has no significant effect on AOP. Between the two of trust antecedents, the EWOM and Perceived Reputation only Perceived Reputation has a significant influence on the Trust. From the four constructs in this study (AOP, OPI, Trust and Perceived Risk), the Trust Model is the most powerful predictive model compared to other models such as Perceived Risk, OPI, and AOP.